Field Evaluation and Diversity of 238 Global Chickpea (Cicer arietinum L.) Genotypes Grown in South-East Kazakhstan - Zatybekov, A.K.; Yeshengaliyeva, A.N.; Anuarbek, Sh.N.; Kudaibergenov, M.S.; Turuspekov, Y.K.; Abugalieva, S.A. (Karagandy University of the name of academician E.A. Buketov, 2025)
A three-year field evaluation was conducted to assess the agronomic performance, trait associations, and diversity of 238 chickpea (Cicer arietinum L.) genotypes from a global collection cultivated under the semiarid conditions of South-East Kazakhstan. The trials, carried out across three growing seasons, recorded significant variation for plant height (PH), height to lowest pod (HLP), number of lateral branches (NLB), number of seeds per plant (NSP), yield per plant (YP), and thousand-seed weight (TSW). Analysis of variance revealed significant effects of genotype origin, seed type, and year for several traits, with strong genotype × environment interactions. Correlation analysis showed that YP was strongly and positively associated with TSW (r = 0.605) and moderately with NSP (r = 0.530), while NSP and TSW were negatively correlated, indicating a trade-off between seed size and seed number. Principal component analysis (PCA) revealed that the genotypes originating from the Middle East and Africa were primarily grouped with higher values for yield per plant (YP) and thousand-seed weight (TSW), whereas South Asian germplasm showed wide phenotypic dispersion, reflecting their broad variability. Kabulitype of chickpea seeds showed a strong association with yield-related traits, while Desi types revealed greater variability and a weaker association with seed size. A total of 24 perspective genotypes, such as ICC456, ICC637, ICC1392, ICC2065, ICC3362, and ICC3410, were identified as valuable candidates for breeding aimed at improving productivity and adaptability of chickpea in South-East Kazakhstan. Overall, these results enhance understanding of the diversity and interrelationships of agronomic traits in global chickpea germplasm and emphasize the breeding potential of selected genotypes for semi-arid regions.
Keywords: semi-arid Kazakhstan; agronomic traits; global collection; chickpea